Field notes contributed by Marion M. Brewer, spring 1996 - Brewer, Marion M.et al (1996)
Spring report of birds found in northwest Iowa contributed by Marion M. Brewer. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1996. Epson - sheet feed